Determining the number of layers in graphene films synthesized by filtered cathodic vacuum arc technique. Issue 11 (1st November 2016) - Kesarwani, A. K.; Panwar, O. S.; Dhakate, S. R.; Singh, V. N.; Rakshit, R. K.; Bisht, Atul; Kumar, Ashish
ABSTRACT: We have synthesized graphene film by the filtered cathodic vacuum arc (FCVA) technique and determined the number of layers in graphene films by various techniques. Amorphous carbon (a-C) films of different thicknesses (1, 2, 3, 6, 10 and 18 nm) were synthesized by the FCVA technique on Si/SiO2 /Ni substrate and then annealed in vacuum at 800°C and cooled down to room temperature naturally to obtain graphene. Prepared graphene films were transferred on different substrates and characterized by the Raman spectroscopy, UV-VIS-NIR spectroscopy, high-resolution transmission electron microscopy (HRTEM), optical microscopy, atomic force microscopy (AFM) and sheet resistance to determine the number of layers present in the graphene films. Raman spectra of the prepared graphene films exhibit that there is red shift in the position of D, G and 2 D peak. The value of I 2D / I G varied from 0.18 to 0.51, I D / I G varied from 0.82 to 1.02 and full width at half maximum of 2 D peak varied from 101.2 to 128.0 cm −1, for different thicknesses of graphene films, respectively. The value of transmittance decreases from 97 to 63.7% and that of sheet resistance increases from 460 to 1400 Ω/square with the increase in the thickness of the prepared graphene film. The HRTEM and AFM study revealed that the graphene synthesis from 1 nm thick a-C film possesses a single layer structure.